Diversity Of Tangkul Catches (Portable Lift Net) In Teluk Lake Olak Kemang Village Danau Teluk Distric Jambi City - Azhariyah, Ayu; Lisna, Lisna; Resmi, Resmi (Program Studi Budidaya Perairan Universitas Mataram, 2024)
Tangkul or lift net is a type of anco fishing gear that differs only in large size. Tangkul is a square, generally measuring 5x5 m with a mesh size varying between 1/4 - 1.5 inches, depending on the fishing season. The purpose of this determine the diversity of tangkul catches (Portable lift net) in Teluk Lake, Olak Kemang Village, Danau Teluk Distric Jambi City. This research was conducted on March 21, 2022 to April 21, 2022. The method used in this research is a survey method, namely by direct observation in the field and conducting interviews with fishermen. The data collected is the catch of tangkul fishing gear which includes the type of fish, the number of catches (tails) and the total weight of the catch (grams). Furthermore, environmental parameters are temperature, degree of acidity (pH), and depth. The results of the research that have been obtained are the composition of tangkul catches, there are 9 species of fish with the highest composition being flatback fish (Thynnichtys polylepis) with a value of 42.52% and the lowest composition being catfish species (Pangasianodon hypophthalmus) with a value of 0.30%. The diversity index (H') obtained with a value of 1.39 is in the medium category, the evenness index (E) obtained with a value of 0.64 is in the high category and the dominance index (C) obtained with a value of 0.30 is in the low category. The conclusion of this study is the diversity index of Tangkul catches (Portable lift net) is in the medium category and no fish species dominate or are included in the low category in Teluk Lake, Olak Kemang Village, Danau Teluk District, Jambi City.